Capability Approach and Good Governance in Strategies to Increase Community Participation in Spatial Planning, East Kalimantan - Firmani, Iqro; Daulay, Pardamean; Rulandri, Novianita (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines strategies for enhancing public participation in spatial planning in East Kalimantan Province, employing a capability approach and principles of good governance. Public participation still faces various obstacles, including limited knowledge, low spatial literacy, restricted access to public information, and inadequate technical support and participatory incentives, particularly in remote areas. This study employs a qualitative method with a descriptive-exploratory design to examine the internal and external factors influencing public participation and to formulate contextual strategies for enhancing participation. The results indicate that efforts to increase public involvement are insufficient by simply adding formal forums; instead, they must be directed at strengthening citizen capabilities through spatial literacy, community facilitation, inclusive technology utilization, and strengthening local institutions. Although participation policies have been stipulated in various regulations, their implementation has not been optimal and tends to be procedural. Therefore, strategies for increasing participation must be transformative and collaborative, and position the public as active subjects in the spatial planning process. With this approach, public participation can be a key instrument for realizing democratic, inclusive, and socially just spatial planning amidst the dynamics of East Kalimantan's development after the establishment of the National Capital City.